Studying the Stress Response across Tissues in House Sparrows; A Dive into the Rest of the Picture through the Lens of DNA damage - Estrada, Rodolfo S. (Tufts Archival Research Center, 2020)
This project delved into the ongoing assessment of stress in vertebrates through DNA damage. By applying a technique previously used only to measure damage in blood, this work explored the physiological implications of stress across various tissues and adds context to the biological implications of blood DNA damage.